Indonesian Version of the Risk-Taking and Self-Harm Inventory for Adolescents: Validation and Psychometric Testing - Munisa, Munisa (Kuras Institute, 2025)
Self-harm in adolescents is becoming an issue of increasing concern, especially due to increased exposure to content on social media that can influence their behaviour. Adolescents who are experiencing emotional distress often use self-harm as a coping mechanism to deal with stress, anxiety, or feelings of helplessness. The development of an Indonesian version of this instrument is necessary to provide a valid and reliable measurement tool appropriate to the local cultural context in identifying tendencies towards self-harm and risk-taking behavior in the adolescent population in Indonesia. The aim of this research is to develop an Indonesian of the risk-taking and self-harm inventory for adolescents (SHIA). A sample of N = 446 participants was approached through an online survey created using google forms, a free online survey tool. Data were collected from various universities in Indonesia, 84 male students (18.8%) and 362 female students (81.2%). SHIA-18, with four aspects, namely: 1) mutilation, (2) self-harm, (3) overdose, and (4) suicide attempts. Data were analysed using a Rasch model approach. The findings of this research produced the SHIA-18 which has satisfactory psychometric properties as a valid and consistent tool for assessing the level of self-harm in adolescent, consisting of 18 items. The tool demonstrated strong internal consistency and measurement properties, and its performance was found to be invariant across gender.